Answer:
complete the missing value in the solution
Explanation:
Simplifying
6x + 7y = 4x + 4y
Solving
6x + 7y = 4x + 4y
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '-4x' to each side of the equation.
6x + -4x + 7y = 4x + -4x + 4y
Combine like terms: 6x + -4x = 2x
2x + 7y = 4x + -4x + 4y
Combine like terms: 4x + -4x = 0
2x + 7y = 0 + 4y
2x + 7y = 4y
Add '-7y' to each side of the equation.
2x + 7y + -7y = 4y + -7y
Combine like terms: 7y + -7y = 0
2x + 0 = 4y + -7y
2x = 4y + -7y
Combine like terms: 4y + -7y = -3y
2x = -3y
Divide each side by '2'.
x = -1.5y
Simplifying
x = -1.5y